2004
DOI: 10.1074/jbc.m404882200
|View full text |Cite
|
Sign up to set email alerts
|

Intron Retention Generates a Novel Id3 Isoform That Inhibits Vascular Lesion Formation

Abstract: The expression of intron-containing messages has been shown to occur in a variety of diseases including lactic acidosis, Cowden Syndrome, and several cancers. However, it is unknown whether these intron-containing messages result in protein production in vivo. Indeed, intron-containing RNAs are typically retained in the nucleus, targeted for degradation, or are repressed translationally. Here, we show that during vascular lesion formation in rats, an alternative isoform of the helix-loop-helix transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 25 publications
3
56
0
3
Order By: Relevance
“…24 This isoform, in contrast to Id3, seems to attenuate growth of smooth muscle cell during vascular lesion formation by inducing apoptosis. 23,24 Unlike Id3 and Id3a, SOM1 and SOM3 are coexpressed in normal tissues and in primary human EC (Ting et al 6 and this study), but similar to Id3, they have opposing effects. Whereas Id proteins sequester basic helix-loop-helix factors, thereby preventing them from binding to DNA and activating transcription, 25 both SOM-isoforms are active transcription factors on their own.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This isoform, in contrast to Id3, seems to attenuate growth of smooth muscle cell during vascular lesion formation by inducing apoptosis. 23,24 Unlike Id3 and Id3a, SOM1 and SOM3 are coexpressed in normal tissues and in primary human EC (Ting et al 6 and this study), but similar to Id3, they have opposing effects. Whereas Id proteins sequester basic helix-loop-helix factors, thereby preventing them from binding to DNA and activating transcription, 25 both SOM-isoforms are active transcription factors on their own.…”
Section: Discussionmentioning
confidence: 99%
“…Id3 can promote cell cycle entry and thereby induce smooth muscle cell proliferation by inhibiting p21 WAF1 and p16 INK4 transcription. 23 An alternatively spliced transcript translates into an isoform with a different C terminus (Id3a), which is not detected in normal rat carotid arteries, but abundantly expressed in the neointimal layer after balloon injury, like its human homolog Id3L in carotid atherosclerotic plaques. 24 This isoform, in contrast to Id3, seems to attenuate growth of smooth muscle cell during vascular lesion formation by inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…One clearly documented example involves some of the members of the Id family of helix-loop-helix (HLH) transcription factors. Specifically, retention of the single small intron in the Id3 gene after vascular injury results in expression of an alternative protein isoform, which appears to function as a modulator of the protein expressed from the spliced RNA (Matsumura et al 2001;Forrest et al 2004). This may be particularly relevant, since a recent study demonstrated that deletion of the WT1(+KTS) isoform affected the expression of MASH1, an HLH transcription factor required for early neurogenesis (Wagner et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, Id3 expression is induced during vascular lesion formation in response to injury. 26,27,41 Herein, we provide evidence that elevated 12/15LO expression at baseline resulted in increased postinjury Id3 expression. Moreover, loss of Id3 attenuated the increased neointimal Ki-67-positive staining in the injured 12/15LO-tg animals, providing evidence that Id3 is essential for 12/15LO-induced vascular wall proliferation.…”
Section: Discussionmentioning
confidence: 88%